PENGABDIAN MASYARAKAT TENTANG EDUKASI MENCEGAH INFEKSI DENGAN MENCUCI TANGAN YANG BENAR PADA SISWA/I SD COT PREH ACEH BESAR - Nurul Amna; Khaira Rizki; Ellyza Fazlylawati; Dara Agustina; Ayu Maisarah; Saidi Umar; Winda Permatasari; Silvi Ferislan; Hayatun Nisa; Erika Mayani (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Background: Diabetes mellitus is a degenerative disease characterized by high blood sugar levels caused by disturbances in insulin secretion in the body. Insulin is a hormone that helps control sugar levels in the body. Purpose of service: Providing health education about diabetes mellitus to the community. Method: The method used in this service activity is lecture and question and answer. Results: Shows that counseling can increase each individual's knowledge. Pretest 48% and Posttest 78%. Conclusion: By providing health education to the public, knowledge can be increased and have an impact on improving the level of public health